Automated Product Suggestions with Needs-based ConƖgurators - Johanna Hasenmaile-Aspin; Philipp Scharfenberger (Marketing Review St.Gallen, 2020)
Increasingly complex product portfolios make it more relevant than ever to match the right product to the right consumer. We show how needs-based configurators help to optimize consumer's choice processes by providing automated individualized product suggestions.
Keywords: 650